Long-term treatment outcomes with a single 0.19 mg fluocinolone acetonide implant in non-infectious uveitis: a real-world study - Darwisch, Warda; Waizel, Maria della Volpe; Finger, Robert P.; Januschowski, Kai; Seitz, Berthold; Fries, Fabian Norbert; Rickmann, Annekatrin (Ocular immunology and inflammation, 2025)
To evaluate time to first additional treatment following intravitreal 0.19 mg fluocinolone acetonide (FAc) in non-infectious uveitis with posterior segment involvement (NIU-PS) in a real-world setting. Prospective observational study on 37 eyes (30 patients) with chronic or recurrent NIU-PS, treated with FAc after achieving control - indicated by absence of vitreous haze or clearly visible posterior pole. Over a median follow-up of 48.0 ± 0.0 months, we assessed time to and number of additional treatments, inflammatory activity, central subfield macular thickness (CSMT), visual acuity (VA) and intraocular pressure (IOP). Restricted mean time to first adjuvant treatment was 31.9 ± 2.97 months, with 52.8% requiring no additional treatment ≥ 48 months. VA remained stable (baseline 0.56 ± 0.44 logMAR, p = 0.86). A negative correlation was found between the number of prior steroid implants (DEX-I) and time to additional treatment (r = −0.44, p = 0.001). For up to 24 months, FAc reduced anterior chamber flare (0.44 ± 0.81 to 0.00 ± 0.00, p < 0.001), vitreous haze (0.28 ± 0.51 to 0.00 ± 0.00, p = 0.01), and CSMT (407.1 ± 135.9 µm at baseline to 324.2 ± 75.7 µm at M24, p = 0.001). Within 48 months, ocular hypertension (≥25 mmHg) occurred in 22.2% of eyes (8/36), with 19.4% (7/36) requiring new-onset IOP-lowering drops. FAc demonstrated efficacy in managing low-grade NIU-PS, reducing the need for additional treatments and controlling intraocular inflammation for an average of 32 months.